DAMPAK BULLYING TERHADAP KESEHATAN MENTAL - Yulianti Yulianti; Ipa Pakpahan; Dila Angraini; Resty Ayunabilla; Alma Aura Febia; Muhammad Iham Habibi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to explore the impact of bullying on individual mental health, especially in children and adolescents. A qualitative approach is used to understand the experiences and perceptions of bullying victims, as well as the psychological and social impacts they have. Through in-depth interviews with bullying victims, parents, teachers and school staff, as well as participatory observation in the school environment, data was collected and analyzed using thematic analysis techniques. Findings show that victims of bullying often experience depression, anxiety, sleep disorders, and feelings of insecurity and protection in the school environment. This impact not only impacts the victim's mental health directly, but also impacts their overall quality of life. Therefore, effective preventive and intervention measures are needed to overcome the problem of bullying, including increasing awareness, creating a safe environment, and providing support for victims. This research makes an important contribution to the understanding of the impact of bullying on mental health, and strengthens the urgency to create environments that are free from bullying and support the psychological well-being of children and young people.